Special Issue: Chinese Buddhism from Holmes Welch to the Present - Fisher, Gareth (Review of Religion and Chinese Society, 2020)
"Special Issue: Chinese Buddhism from Holmes Welch to the Present" published on 20 May 2020 by Brill.